PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU DIMODERASI IKLIM ORGANISASI (STUDY PADA SMP MUHAMMADIYAH SE KABUPATEN PATI) - Lely Kaindah, 12.5202.0259 (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study aimed to examine the effect of competence and motivation towardorganizational climate moderated Teacher Performance (Studies in SMPMuhammadiyah of pati regency). This study included in the quantitative data withmengguna primary data obtained from the questionnaire. The method used in this study is in the form of questionnaires in which thepopulation of as many as 99 teachers, while the data is processed as a teacher.Measurements using a Likert scale with seven (7) alternative answers. Test instrumentsused are validity and reliability. While the test model used is the coefficient ofdetermination (R2) and the F test (goodnes of Fit). Test this hypothesis using regressionanalysis. Based on the results of the study can be summarized as follows: (i)Competence positive and significant impact on teacher performance, (ii) Motivationpositive effect on teacher performance, (iii) organizational climate positive andsignificant impact on teacher performance, (iv) a positive organizational climate andsignikan on teacher performance, (v) strengthening the organizational climate influenceon the performance of the competence and motivation of teachers.Keywords: COMPETENCE, MOTIVATION, CLIMATE ORGANIZATION AND TEACHER PERFORMANCE